Knowledge mapping of the links between the microbiota and allergic diseases: A bibliometric analysis (2002–2021) - Lv, Hao; Wang, Yunfei; Gao, Ziang; Liu, Peiqiang; Qin, Danxue; Hua, Qingquan; Xu, Yu (Frontiers in Immunology, 2022)
Background: In recent decades, dramatic changes in modern environmental exposures and lifestyles have resulted in a steep rise in the prevalence of allergic diseases such as asthma, allergic rhinitis, atopic dermatitis and food allergies. Evidence is mounting that the microbiota plays a crucial role in allergic disorder development and evolution. Therefore, a better understanding of allergic diseases within the context of the microbiota is urgently needed. This work aimed to comprehensively outline general characteristics, research hotspots, evolution routes, and emerging trends in this area. Methods: Relevant publications from January 2002 to December 2021 were obtained from the Web of Science Core Collection on 5 August 2022. Bibliometric and visual analyses were performed using CiteSpace; VOSviewer; an online bibliometric platform; and Microsoft Excel 2019. Results: In total, 2535 documents met the requirements. The annual number of publications has shown rapid growth in the last two decades. The USA, University of California System, and Isolauri E of the University of Turku were the most productive and influential country, institution, and author, respectively. The Journal of Allergy and Clinical Immunology was the most prolific and most cocited journal. High-frequency keywords included “gut microbiota”, “asthma”, “atopic dermatitis”, “children”, and “probiotics”. Recent studies have focused on “atopic dermatitis”, “skin”, “asthma”, and “probiotics”, according to the cocitation analysis of references. Burst detection analysis of keywords showed that “community”, “skin microbiome”, “microbiome”, “Staphylococcus aureus”, and “chain fatty acid” were emerging research frontiers, which currently have ongoing bursts. Conclusion: In the last 20 years, studies of the microbiota in allergic diseases have been flourishing, and the themes have been increasing in depth. These findings provide valuable references on the current research hotspots and gaps and development trends in the link between the microbiota and allergic diseases.